2010
DOI: 10.1080/10286020.2010.486378
|View full text |Cite
|
Sign up to set email alerts
|

A new prenylated isoflavone from Derris scandens Benth

Abstract: The phytochemical study of the whole plant of Derris scandens (Leguminosae) has resulted in the isolation of a new isoflavone derivative, scandinone A (11), together with 11 known compounds (1-10, 12). Structural elucidations of these compounds were performed using spectroscopic methods especially 1D, 2D NMR, and mass spectral analyses. The alpha-glucosidase-inhibitory activity of the isolates was also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…An unrelated study on the same species (cited as Psoralea corylifolia) reports bavarigenin (34) as a constituent of dried ripened fruits. 59 Only 4 examples of O-prenylated isoavones are recorded among the compounds discussed in this section (35,56,57,62). The rst of these, 7-O-prenylbiochanin A (35), was known previously as a synthetic product, 60 but has now been obtained from the root bark of Dalbergia sissoo.…”
Section: Isoflavonesmentioning
confidence: 99%
See 1 more Smart Citation
“…An unrelated study on the same species (cited as Psoralea corylifolia) reports bavarigenin (34) as a constituent of dried ripened fruits. 59 Only 4 examples of O-prenylated isoavones are recorded among the compounds discussed in this section (35,56,57,62). The rst of these, 7-O-prenylbiochanin A (35), was known previously as a synthetic product, 60 but has now been obtained from the root bark of Dalbergia sissoo.…”
Section: Isoflavonesmentioning
confidence: 99%
“…61 Hexane extracts of the whole plant of Derris scandens contain numerous 6,8-diprenylated derivatives of genistein and its methyl ethers, of which scandinone A (36) is a new example. 62 The structure of the linear pyranoisoavone erythraddison A (37) is notable for the unusual hydroxymethyl substituent at C-8 of the A-ring.…”
Section: Isoflavonesmentioning
confidence: 99%
“…Its root can be used as an insecticide, diuretics and elixirs [2]. Moreover, several properties of this plant were reported in academic journal such as it showed the inhibitory effect of natural killer cell (NK cell) on HIV-infected patients [3], inhibited the activity of -glucosidase for antidiabetic therapeutics [4,5], antimigration of cancer cells [6]. Its anti-inflammatory property is interesting in this research because it was found to be the most active traditional Thai medicine to reduce inflammation [7].…”
Section: List Of Figuresmentioning
confidence: 99%